2011
DOI: 10.15835/nbha3915713
|View full text |Cite
|
Sign up to set email alerts
|

Seed Development and Quality in Maize Cultivars

Abstract: In order to evaluate seed development and quality of maize (Zea mays) cultivars ('DC-370' , 'SC-500' , 'OSSK-602' and 'SC-604'), a split plot experiment (using R.C.B. design) with three replicates was conducted in 2009 at the Research Farm of the Faculty of Agriculture, University of Tabriz, Iran. Seeds were harvested at five day intervals in eight stages. Subsequently, the quality of seed samples was determined in the laboratory. Germination percentage and seedling dry weight were enhanced, but electrical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Given that we had no information about the regulation of expression for the various genes, we used Equation to represent the overall gene expression dynamics of any given gene as a piecewise defined function (see Experimental Procedures). This approach allowed us to phenomenologically account for the various shifts in gene expression levels that are known to occur as endosperm goes through its various developmental stages in maize and other plants (Fraser et al ., ; Ghassemi‐Golezani et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Given that we had no information about the regulation of expression for the various genes, we used Equation to represent the overall gene expression dynamics of any given gene as a piecewise defined function (see Experimental Procedures). This approach allowed us to phenomenologically account for the various shifts in gene expression levels that are known to occur as endosperm goes through its various developmental stages in maize and other plants (Fraser et al ., ; Ghassemi‐Golezani et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We did this by using the GMA representation, a mathematical formalism based on approximation theory (Voit and Savageau, ; Voit, ), and allowing for the parameter optimization process to identify time points at which basal metabolic and gene expression activities could change, resulting in piecewise differential equations. This provided a heuristic way to capture changes in promoter activities that are well known to occur during the development of maize endosperm (Fraser et al ., ; Ghassemi‐Golezani et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It had been reported that seed vigour attained a maximum value when the seed dry weight reached a maximum value, and after that, seed viability and vigour were significantly reduced . The hundred‐grain weight of maize seeds linearly increased with progressing seed development up to 55 days after pollination; the percentage of seed germination increased with enhancing seed weight . However, it was observed that the highest seed quality of cowpea was attained at physiological maturity (52–56 days after pollination) which occurred 8–16 days after the end of the seed filling period or mass maturity .…”
Section: Introductionmentioning
confidence: 99%
“…Stage of maturity at harvest is one of the most important factors that can influence the vigor of seeds (Demir et al, 2008). Maximum seed vigor on the mother plant may be achieved at the end of seed filling phase (mass maturity) which is also described as physiological maturity (Harington, 1972;Ghassemi Golezani et al, 2011b) or after mass maturity (Ghassemi-Golezani and MazloomiOskooyi, 2008;Ghassemi-Golezani et al, 2011a), depending on species and seed testing methods (Tekrony and Egli, 1997;Ghassemi-Golezani and Hosseinzade-Mahootchi, 2009). Vieira et al, (1992) reported that drought stress had no significant effect on soybean seed germination and vigor.…”
Section: Introductionmentioning
confidence: 99%